2020
DOI: 10.1007/s11332-020-00651-5
|View full text |Cite
|
Sign up to set email alerts
|

A three-experiment examination of iliotibial band strain characteristics during different conditions using musculoskeletal simulation

Abstract: Iliotibial band syndrome (ITBS) is a common chronic pathology mediated via excessive Iliotibial band (ITB) strain. The purpose using a three-experiment approach is to provide insight into the differences in strain between different athletic movements, the incidence of ITBS in females, the efficacy of different prophylactic modalities for ITBS and also the kinematic parameters associated with ITB strain. METHODS: Experiment 1 examined male and female athletes performing run, 45° cut and one-legged hop movements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The increases in the hip adduction and knee internal rotation angles were found to be related to the causes of a higher ITB strain rate [ 7 , 8 ]. Sinclair et al [ 9 ] examined different movements, including running, cutting, and hopping, which indicated that running and cutting resulted in a higher amount of strain than hopping. Additionally, a narrower step width was revealed to increase the ITB strain rate significantly when compared to a preferable condition [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increases in the hip adduction and knee internal rotation angles were found to be related to the causes of a higher ITB strain rate [ 7 , 8 ]. Sinclair et al [ 9 ] examined different movements, including running, cutting, and hopping, which indicated that running and cutting resulted in a higher amount of strain than hopping. Additionally, a narrower step width was revealed to increase the ITB strain rate significantly when compared to a preferable condition [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high incidence of lateral ankle sprain injuries (4) and the poor-long term prognosis following injury (7), prophylactic/ preventative strategies are a key priority for clinical sports research (13). The ankle joint can theoretically be supported by external equipment (14), therefore devices such as ankle braces and sleeves as well as athletic footwear with different collar heights and traction characteristics have received considerable attention.…”
Section: Introductionmentioning
confidence: 99%